If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = -2(4 + 3x) + 7(x + 4) 28 = (4 * -2 + 3x * -2) + 7(x + 4) 28 = (-8 + -6x) + 7(x + 4) Reorder the terms: 28 = -8 + -6x + 7(4 + x) 28 = -8 + -6x + (4 * 7 + x * 7) 28 = -8 + -6x + (28 + 7x) Reorder the terms: 28 = -8 + 28 + -6x + 7x Combine like terms: -8 + 28 = 20 28 = 20 + -6x + 7x Combine like terms: -6x + 7x = 1x 28 = 20 + 1x Solving 28 = 20 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 28 + -1x = 20 + 1x + -1x Combine like terms: 1x + -1x = 0 28 + -1x = 20 + 0 28 + -1x = 20 Add '-28' to each side of the equation. 28 + -28 + -1x = 20 + -28 Combine like terms: 28 + -28 = 0 0 + -1x = 20 + -28 -1x = 20 + -28 Combine like terms: 20 + -28 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| (X-8)14=28 | | 4(2u+2)-12u= | | 4(5x-5)=20(x+1) | | 4(2u+2)-12= | | 5(x+3)=9x+43 | | (-5)(4-5x)=7-3(3x-9) | | 7w+21=-5(w+3) | | -3g-7=-7-2g | | 33-x=26 | | 7x+10=6x+17 | | -(x+3)+6x= | | 23-x=17 | | 9x^2-17=-16 | | -7(1+4x)=217 | | 6x+9=4x+25 | | 8-7j=-6j | | 12+1y+3y=28 | | (2x-1)/3=5x-6/4 | | 2x-9=3x+0 | | 4=-2(4.50+25p) | | -32-8x+6x=12 | | -3(w+1)-4= | | 58=3x+4x+2 | | p=5+2q | | 4=-2(4.50+25) | | 3X*2-12X=2X+7 | | 19+169r^2=380 | | 2.1x-2.16=0.84-5.4 | | 5w=6w-8 | | 5x+2x-6=43 | | 3(2u-3)-2(u+4)= | | 5p^2-17=28 |